Features of Emotional Sphere in Speech Therapist Teachers and their Reflection in Language Action - A N Leyeva; N A Fomina (Peoples' Friendship University of Russia (RUDN University), 2014)
The article is devoted to disclosing the features of the emotional sphere of teachers working with children with speech disorders and their manifestations in speech activity.